Variation of boundary layer heights and eddy diffusivities over dry and moist convective regions of monsoon trough during different phases of monsoon - PADMANABHAMURTY, B.; JAIN, INDU (MAUSAM, 1999)
Temperature, wind, and humidity data at 6 levels over meteorological towers at Kharagpur and Jodhpur and fast data at Jodhpur (Sonic anemometer at 4m and Gill anemometer 15 m) and Kharagpur (Sonic anemometer at 8m and Gill anemometer at 15m) were analysed. Diurnal variation of boundary layer heights and eddy diffusivity coefficient of moment, heat and moisture at dry convective region Jodhpur (26° N, 73°E) and moist convective region Kharagpur (22.3°N, 87.2°E) of monsoon trough during onset of monsoon, mid-monsoon and end-monsoon phases of the Indian southwest monsoon are studied using micro meteorological tower data. Boundary layer height is computed by eddy correlation (direct method) and profile method {indirect method). Indirect method underestimates the boundary layer height.